2017
DOI: 10.1186/s13287-017-0730-z
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of murine mesenchymal stem cells synergistically enhanced immunomodulation and osteogenesis

Abstract: BackgroundMesenchymal stem cells (MSCs) are capable of immunomodulation and tissue regeneration, highlighting their potential translational application for treating inflammatory bone disorders. MSC-mediated immunomodulation is regulated by proinflammatory cytokines and pathogen-associated molecular patterns such as lipopolysaccharide (LPS). Previous studies showed that MSCs exposed to interferon gamma (IFN-γ) and the proinflammatory cytokine tumor necrosis factor alpha (TNF-α) synergistically suppressed T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 53 publications
3
93
0
Order By: Relevance
“…Moreover, hormetic bi‐phasic dose‐responses may be involved in the process of macrophage reprogramming and polarization that is produced by chemicals, as well as ionizing radiation (Genard, Lucas & Michiels, ; Walton, ; Wu et al, ). Other studies have shown that preconditioning‐induced protection responses are associated with increased M2 polarization across multiple organs/cell types (e.g., bone, Young et al, ; spinal cord, Hayakawa et al, ; mesenchymal stem cells, Lin et al, , Mountziaris, Tzouanas, & Mikos, ; Kidney, Hato et al, ) reflecting the generality of the adaptive strategy. These findings suggest that hormetic mechanisms may play a role in mediating M1 or M2 macrophagic cell (e.g., microglial) phenotypes that respectively mediate pro and/or anti‐inflammatory functions that are likely operative in pathologic and adaptive processes.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, hormetic bi‐phasic dose‐responses may be involved in the process of macrophage reprogramming and polarization that is produced by chemicals, as well as ionizing radiation (Genard, Lucas & Michiels, ; Walton, ; Wu et al, ). Other studies have shown that preconditioning‐induced protection responses are associated with increased M2 polarization across multiple organs/cell types (e.g., bone, Young et al, ; spinal cord, Hayakawa et al, ; mesenchymal stem cells, Lin et al, , Mountziaris, Tzouanas, & Mikos, ; Kidney, Hato et al, ) reflecting the generality of the adaptive strategy. These findings suggest that hormetic mechanisms may play a role in mediating M1 or M2 macrophagic cell (e.g., microglial) phenotypes that respectively mediate pro and/or anti‐inflammatory functions that are likely operative in pathologic and adaptive processes.…”
Section: Discussionmentioning
confidence: 98%
“…Mouse MSCs were treated with 20 mg/ml LPS for 24 h or otherwise as indicated below. The dose of LPS was determined based on a previous study (10). The trained MSCs were washed by PBS and incubated with fresh medium without LPS for 3 d before the secondary stimulations (Fig.…”
Section: Preparation Of Trained Mscs and Macrophagesmentioning
confidence: 99%
“…Recent studies indicate that proinflammatory stimulation may have prolonged effects on the function of MSCs. MSCs preconditioned by transient exposure to inflammatory cytokines alone or combined with PAMP enhanced immunomodulation and tissue regeneration (10)(11)(12). We recently observed that when MSCs were exposed to LPS repeatedly, NF-kB activation was significantly increased compared with single LPS exposure (13).…”
mentioning
confidence: 99%
“…The biological responses of MSCs to inflammatory stimulation could further enhance the immunomodulatory and tissue regenerative abilities of MSC‐based therapy . Indeed, by simulating the proinflammatory environment, we found that MSCs preconditioned with TNFα and LPS synergistically enhanced osteogenic capacity . Expression of Arg 1 and CD206 in macrophages co‐cultured with the preconditioned MSCs was increased.…”
Section: Introductionmentioning
confidence: 89%
“…Due to these properties, MSC‐based therapy has been applied in more than 400 clinical trials including bone regeneration and chronic inflammatory diseases . The biological responses of MSCs to inflammatory stimulation could further enhance the immunomodulatory and tissue regenerative abilities of MSC‐based therapy . Indeed, by simulating the proinflammatory environment, we found that MSCs preconditioned with TNFα and LPS synergistically enhanced osteogenic capacity .…”
Section: Introductionmentioning
confidence: 90%